Exploration of Teachers' Competencies in Welcoming Deep Learning Based on Mindful, Meaningful, and Joyful Learning (MMJ) - Helwiyah Makarim; Yusuf Haryanto; Ana Ratnasari; Resya Fakhrunnisa (Al-Qalam Institue, 2026)
This study aims to explore teachers’ competencies in addressing students’ learning needs within the implementation of the Kurikulum Merdeka and to identify essential competencies for supporting deep learning practices. The study employed a mixed-method approach with exploratory qualitative dominance. Data were collected through closed-ended questionnaires administered to 40 teachers, in-depth interviews with 5 teachers, and a literature review examining trends in the implementation of the Kurikulum Merdeka. The findings reveal that teachers positively perceive the flexibility offered by the curriculum; however, they still encounter difficulties in designing learning experiences that integrate mindful, meaningful, and joyful learning principles. The study identified six key competencies that need strengthening to support effective deep learning implementation: critical thinking, empathy, reflection, collaboration, adaptation, and humanization. These findings indicate that teachers require a more contextual, reflective, and value-based competency development approach. The study proposes the BERKAH framework as a conceptual model for strengthening teacher competencies in deep learning practices. The implications of this study highlight the importance of developing teacher professional training programs grounded in the BERKAH framework to enhance the quality of elementary education. Further research is recommended to validate and test the effectiveness of the framework in broader educational contexts.